Renal Replacement Therapy in the Pediatric Critical Care Unit - Wang, Shihtien (Journal of Pediatric Intensive Care, 2016)
Renal replacement therapy is becoming more prevalent in the pediatric intensive care units for a large variety of disease states, including multiorgan dysfunction syndrome, fluid overload, and electrolyte imbalance. Three modalities—continuous renal replacement therapy, hemodialysis, and peritoneal dialysis—are commonly used. When deciding among the three therapies, there are several advantages and disadvantages of each modality that must be considered. This manuscript provides an overview of each modality as well as its pros and cons.
Keywords: continuous renal replacement therapy; hemodialysis; peritoneal dialysis; dialysis modalities